HASIL BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI MODEL PEMBELAJARAN SISWA AKTIF - Deki Putrama Al-Khairi; Zulfani Sesmiarni; Rodi Rodi; Adeng Putra (CV. ADIBA AISHA AMIRA, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) at UPTD SDN 02 Guguak through the application of an active student learning model. The method used is classroom action research (CAR) with two cycles, involving planning, implementation, observation, and reflection. The subjects of the study consisted of 15 fourth grade students. Data were collected through learning outcome tests, observations, and interviews. The results showed a significant increase in student learning outcomes, with an average test score before the action of 65.5 and increasing to 82.3 after the application of the active student learning model. These findings indicate that the active student learning model can increase student motivation and engagement, and have a positive impact on PAI learning outcomes. This study suggests that teachers consider implementing this model in learning to improve the quality of education in schools.